A novel L1C.5 RFLP-1-4-4 recombinant porcine reproductive and respiratory syndrome virus between wild-type virus and a modified-live virus vaccine is highly pathogenic to piglets - Gao, Xue; Zhou, Jun; Kang, Runmin; Lu, Haohao; Feng, Shuo; Pei, Yiwen; Liu, Jie; Zhang, Zhidong; Zhou, Long (Frontiers in Veterinary Science, 2025)
Porcine reproductive and respiratory syndrome (PRRS) is a severe viral disease in pigs caused by porcine reproductive and respiratory syndrome virus (PRRSV). It poses a severe threat to the global swine breeding industry. Recently, the emergence of PRRSV lineage 1C.5 in the United States and China with the RFLP 1–4-4 pattern has raised worldwide attention; however, there are few studies on the genome and pathogenic characteristics of the L1C.5 RFLP 1–4-4 PRRSV in China. In this study, a novel PRRSV-2 variant, designated GX2024, was isolated from a RespPRRS MLV-vaccinated piglet in China using Marc-145 cells and porcine alveolar macrophages (PAMs). The complete viral genome was further determined and analyzed. Phylogenetic analysis of its ORF5 gene showed that GX2024 belonged to PRRSV-2 L1C.5 (RFLP-1-4-4) group, whereas the complete genome sequence clustered into L8E (JXA1-like) group and it contains a discontinuous 131-aa deletion in NSP2 when compared to the NADC30 strain. Notably, recombination analyses indicated that GX2024 is a multiple recombinant virus from two wild-type PRRSVs L1C.5 (NADC30-like) and L8E (JXA1-like), and a RespPRRS MLV vaccine (L5A) strain. To tested the pathogenicity of GX2024, nine four-week-old piglets were divided into two groups (GX2024-challenge group, n = 5; negative control, n = 4). GX2024 infection caused high fever (40–42°C) and severe hemorrhagic pneumonia with pulmonary edema. The lymph nodes exhibited obvious hemorrhagic spots with lymphadenopathy. Of note, all GX2024-infected piglets died within 14 days with 100% mortality, indicating that GX2024 is a highly pathogenic PRRSV strain. Our study reports the emergence of a novel highly pathogenic L1C.5 RFLP-1-4-4 recombinant strain, which merits special attention in control and vaccine strategies in China.